Concerning the Issue of Knowledge Management: Theory, Models, Methods - I. G. Gorina; N. M. Fomenko (Вестник Российского экономического университета имени Г. В. Плеханова)
Within the frames of new system management shaping it becomes necessary to transform mechanisms of competitive advantage. Today three spheres of activity were selected: scientific, technological and personnel from all the priority fields of governmental level. The development and maintenance of scientific and personnel spheres are not possible without a unified system affecting creation, acquisition and efficient use of knowledge. In unstable economic conditions topicality of introducing knowledge management system in organizations is especially valuable. The article studies preconditions of the theory of knowledge management, the idea of post-industrial society and economy of knowledge. The authors characterized types of knowledge, showed value of knowledge in conceptions of organizational management and implicit knowledge. When theoretical aspects of knowledge management models were investigated, the parallel between shaping the system of knowledge management with intellectual capital and intangible resources was drawn. Theoretic aspects of the system of knowledge management were studied within the frames of systematic approach as a universal investigation tool.